Dilemma And Depression Living As A Woman In Rebecca Miller's Movie The Private Lives Of Pippa Lee (2009): A Psychoanalytic Approach - ILHAM, YULIAN (2012)
The problem of the study is to reveal how major character reflects her dilemma and depression living as a woman. The objective of the study is to analyze the film based on the structural analysis and based on the psychoanalytic analysis. The research is qualitative research. Type of data of the study is text and image from two data sources: primary and secondary. The primary data source is The Private Lives of Pippa Lee movie directed by Rebecca Miller released in 2009. While the secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusion. First, based on the structural analysis of each elements, it shows that the character and characterization, casting, plot, setting, point of view, theme, mise en scene, cinematography, sound, and editing are related one another and form of unity. Second, based on the psychoanalytic analysis, the writer concludes that the problems of the major character cause the conflict of her mental condition. It happens when there is contradiction between Id, Ego, and Superego and it brings her into dilemma and depression living as a woman.